EMPTY EVERYWHERE; OUTFLOWING WITHIN - Fung, Jojo M. (Asian Horizons, 2020)
In the light of the lockdown due to COVID-19, this article offers a theological reflection on the emptiness of the streets and the churches and how this pandemic has facilitated the outflow of contemplative richness from within the hitherto untapped wellsprings of many believers and the creativity of the Church. The pandemic has generated forthcoming narratives related to the victorious Peoples’ War, xenophobic Orientalism, electropollution, pharma-elitism, genetic studies and ecological factors. Moreover, this pandemic has ushered in the era of mysticalone in which there is a heightened awareness of the actions of Rûah Elohim in the age of pneumatolocene in terms of contemplativity, sacrificial spirit, and spirt of Prophetic voice